Preceramic paper-derived SiCf/Ti3Al(Si)C2 and SiCf/Ti3SiC2 MAX-phase based laminates fabricated using spark plasma sintering. (15th March 2021) - Kashkarov, E.B.; Pushilina, N.S.; Syrtanov, M.S.; Krotkevich, D.G.; Gotman, I.; Travitzky, N.
Abstract: For the first time SiCf /Ti3 Al(Si)C2 and SiCf /Ti3 SiC2 MAX-phase based laminates were fabricated from preceramic papers by spark plasma sintering (SPS). The fibers were coated with a 4-µm layer of carbon by chemical vapor deposition. The phase composition and microstructure were analyzed by X-ray diffraction and scanning electron microscopy, respectively. The flexural strength of Ti3 Al(Si)C2 -based laminates with carbon coated SiC fibers was 990 MPa, which is 20% higher compared to laminates with uncoated fibers. The carbon coating prevents chemical reaction between the fiber layers and MAX-phase based laminates, providing toughening mechanisms associated with fiber detachment and pull-out. No significant reaction of the fibers occurs during the sintering of SiCf /Ti3 SiC2 based laminates, which has a flexural strength of 850 MPa. The layer-by-layer reinforced structure of laminates along with the presence of strengthening phases (TiC and Al2 O3 ) provides toughening mechanisms due to deflection and branching of cracks at macro and micro scales. Graphical abstract: Image, graphical abstract